The Role of the Pamong Praja Police Unit in the Control of Street Vendors (PKL) in Stabat District, Langkat Regency - Dameka Putra Singarimbun; Adam Adam; Heri Kusmanto (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2025)
Controlling street vendors (PKL) in Stabat District, Langkat Regency, is a crucial responsibility of the Civil Service Police Unit (Satpol PP) to ensure public order and maintain urban aesthetics. However, implementing this regulation is not without challenges, as it involves resistance from street vendors, limited relocation spaces, and socio-economic concerns that affect their livelihoods. This study aims to analyze the performance of Satpol PP in controlling street vendors and identify the factors influencing the success or failure of these efforts. A descriptive research approach was adopted, utilizing interviews, observations, and document analysis as data collection methods. Data were gathered through interviews with government officials, community leaders, and street vendors in Stabat District. The findings indicate that while Satpol PP has carried out its duties effectively, certain obstacles persist. Beyond enforcing regulations, Satpol PP also plays a role in providing guidance and counseling to street vendors, ensuring they understand legal provisions. Additionally, the unit collaborates with relevant agencies and local communities to implement orderly street vendor management. Nevertheless, enforcement efforts continue to face resistance from vendors, insufficient relocation facilities, and a lack of legal awareness among traders. Many street vendors struggle to adapt to new locations due to accessibility concerns, impacting their ability to sustain their businesses. These findings highlight the need for a more integrated approach in street vendor regulation, balancing law enforcement with economic and social considerations.